Synthesis of bis(indolyl)methanes using silica gel as an efficient and recyclable surface - Thurow S. (2012)
Here we describe a simple, clean, and efficient solvent-free protocol for the synthesis of bis(indolyl)methanes promoted by silica gel. The products were obtained in good to excellent yields through the reaction of indoles with cyclohexanone and a range of aldehydes. The silica gel was easily recovered and utilized for further reactions without loss of activity. © 2012 Elsevier Ltd. All rights reserved.